Phytolith Palaeoenvironments at Mumba Rock Shelter - Mercader, Julio; Clarke, Siobhán; Itambu, Makarius; Mohamed, Abdallah; Mwitondi, Musa; Siljedal, Gunnar; Soto, María; Bushozi, Pastory (Frontiers in Ecology and Evolution, 2021)
The rock shelter site of Mumba in northern Tanzania plays a pivotal role in the overall study of the late Pleistocene archaeology of East Africa with an emphasis on the Middle to Later Stone Age transition. We used phytolith analysis to reconstruct general plant habitat physiognomy around the site from the onset of the late Pleistocene to recent times, tallying 4246 individual phytoliths from 19 archaeological samples. Statistical analysis explored phytolith richness, diversity, dominance, and evenness, along with principal components to compare phytolith distributions over the site’s sequence with known plant habitats today. Generally, the phytolith record of Mumba signifies paleoenvironments with analogues in the Somalia – Masai bushland and grassland, as well as Zambezian woodlands.